A comparison of psychotropic medication prescribing patterns in East of England prisons and the general population. (April 2014) - Hassan, Lamiece; Senior, Jane; Frisher, Martin; Edge, Dawn; Shaw, Jenny
While the prevalence of mental illness is higher in prisons than in the community, less is known about comparative rates of psychotropic medicine prescribing. This is the first study in a decade to determine the prevalence and patterns of psychotropic medication prescribing in prisons. It is also the first study to comprehensively adjust for age when making comparisons with the general population. Four East of England prisons, housing a total of 2222 men and 341 women were recruited to the study. On census days, clinical records were used to identify and collect data on all prisoners with current, valid prescriptions for hypnotic, anxiolytic, antipsychotic, antimanic, antidepressant and/or stimulant medication, as listed in chapters 4.1 to 4.4 of the British National Formulary. Data on 280, 168 patients were obtained for comparison purposes from the Clinical Practice Research Datalink. After adjusting for age, rates of psychotropic prescribing in prison were 5.5 and 5.9 times higher than in community-based men and women, respectively. We also found marked differences in the individual psychotropic drugs prescribed in prison and community settings. Further work is necessary to determine whether psychotropic prescribing patterns in prison reflect an appropriate balance between managing mental illness, physical health risks and medication misuse.